Exploring the role of multiple intelligences: A systematic review for cognitive transformation in biology learning - Muhammad Zahrudin Afnan; Rinie Pratiwi Puspitawati; I. Isnawati (University of Muhammadiyah Malang, 2025)
Traditional approaches to understanding intelligence often overlook the diverse cognitive capacities students possess, limiting inclusivity and educational effectiveness. Howard Gardner's Theory of Multiple Intelligences (MI) offers a comprehensive framework for reconceptualizing how learners process information and develop cognitively. This study explores cognitive transformation through MI theory, analyzing its role in cognitive processes and educational outcomes. Using PRISMA methodology, 1,402 peer-reviewed articles from the Scopus database (2010–2025) were reviewed, employing a descriptive qualitative approach. Findings highlight the distinct roles of Gardner's eight intelligences —linguistic, logical-mathematical, visual-spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, and naturalistic—in cognitive development. Key indicators of transformation include abstract-to-concrete reasoning, concrete-to-abstract conceptualization, and the generation of novel ideas. For instance, naturalistic intelligence fosters ecological understanding in biology, while bodily-kinesthetic intelligence enhances comprehension of physical sciences through experimentation. MI-based pedagogy promotes inclusivity, engagement, and creative problem-solving, underscoring its potential to address cognitive diversity. Future research should focus on empirical testing of MI strategies, developing assessment tools, and leveraging technologies for personalized learning.